Analisis Puisi Chairil Anwar Dengan Judul " Pelarian" Dengan Pendekatan Ekspresif - Esra Polanda Br Simamora (JOURNAL SAINS STUDENT RESEARCH, 2026)
The purpose of this study is to analyze Chairil Anwar's poem "Pelarian" using the expressive method. This method views literary works as expressions of the author's thoughts, feelings, and personal experiences. This study employed a descriptive qualitative approach utilizing text analysis. The research data consisted of words, lines, and stanzas found in Chairil Anwar's poem, which express the poet's emotions and inner attitudes. The analysis shows that Chairil Anwar's poem depicts anxiety, rebellion, and a desire to be free from internal and social pressures. The use of harsh diction, dark imagery, and a highly emotional atmosphere reflect Chairil Anwar's expression as a poet of the '45 generation. Therefore, Chairil Anwar's poem can be considered a representation of the poet's state of mind and his existential attitude towards life. This research is expected to enrich readers' understanding of Chairil Anwar's poetry and the application of the expressive approach in literary studies.